2011
DOI: 10.2116/analsci.27.225
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Liquid Plug Flow-through Polymerase Chain-Reaction System Based on a Heat-Resistant Resin Chip

Abstract: Flow-through polymerase chain reaction (PCR) microfluidic systems for fast, small-volume DNA amplification on a single chip are significantly impacting medical and bioanalytical research. We have fabricated an improved, practical flow-through PCR chip by weighting a pressure-sensitive polyolefin (PSP) film onto a cyclo-olefin polymer (COP) substrate. The substrate was cut so as to produce microchannels, and was used to amplify DNA using a small moving liquid plug, in contrast to conventional continuous-flow-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…To construct a CFPCR chip employing one heater or two heaters, the extension regions or the annealing regions are generated by the thermal gradients between the high-temperature and low-temperature regions. In previous studies, the temperature distributions inside the reaction regions were demonstrated numerically and/or experimentally and utilized to ensure that the requisite temperatures for PCR were existed [ 23 , 24 ]. In addition, by the rearrangement and enlargement of the channel geometry at the extension region, the residence time during the extension step can be properly extended to complete PCR [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…To construct a CFPCR chip employing one heater or two heaters, the extension regions or the annealing regions are generated by the thermal gradients between the high-temperature and low-temperature regions. In previous studies, the temperature distributions inside the reaction regions were demonstrated numerically and/or experimentally and utilized to ensure that the requisite temperatures for PCR were existed [ 23 , 24 ]. In addition, by the rearrangement and enlargement of the channel geometry at the extension region, the residence time during the extension step can be properly extended to complete PCR [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, we developed segment‐flow PCR to prevent interruption of continuous flow; in particular, the sample solution is transported as a liquid plug with respect to the gas phase, thus releasing spontaneous air bubbles into the gas phase . This is equivalent to continuous‐flow PCR in that the sample solution is thermally cycled while flowing through multiple temperature zones of a serpentine microchannel.…”
Section: Introductionmentioning
confidence: 99%